Cryptococcus neoformans Escape From Dictyostelium Amoeba by Both WASH-Mediated Constitutive Exocytosis and Vomocytosis - Watkins, Rhys A.; Andrews, Alexandre; Wynn, Charlotte; Barisch, Caroline; King, Jason S.; Johnston, Simon A. (Frontiers in Cellular and Infection Microbiology, 2018)
Cryptococcus neoformans is an environmental yeast that can cause opportunistic infections in humans. As infecting animals does not form part of its normal life-cycle, it has been proposed that the virulence traits that allow cryptococci to resist immune cells were selected through interactions with environmental phagocytes such as amoebae. Here, we investigate the interactions between C. neoformans and the social amoeba Dictyostelium discoideum. We show that like macrophages, D. discoideum is unable to kill C. neoformans upon phagocytosis. Despite this, we find that the yeast pass through the amoebae with an apparently normal phagocytic transit and are released alive by constitutive exocytosis after 80 min. This is the canonical pathway in amoebae, used to dispose of indigestible material after nutrient extraction. Surprisingly however, we show that upon either genetic or pharmacological blockage of constitutive exocytosis, C. neoformans still escape from D. discoideum by a secondary mechanism. We demonstrate that constitutive exocytosis-independent egress is stochastic and actin-independent. This strongly resembles the non-lytic release of cryptococci by vomocytosis from macrophages, which do not perform constitutive exocytosis and normally retain phagocytosed material. Our data indicate that vomocytosis is functionally redundant for escape from amoebae, which thus may not be the primary driver for its evolutionary selection. Nonetheless, we show that vomocytosis of C. neoformans is mechanistically conserved in hosts ranging from amoebae to man, providing new avenues to understand this poorly-understood but important virulence mechanism.